Arc thermal metal spray for the protection of steel structures: An overview - Lee, H.; Ismail, Mohamed; Choe, H. (2015)
© 2015 by De Gruyter. Coating for corrosion protection was popular during the past decade. Thermal spray coating played an important role during that time. In recent years, arc thermal metal spray coating became widely used. Arc thermal metal spraying method (ATMSM) provides proven long-term protective coating systems using zinc, aluminum, and their alloys for steel work in a marine environment. This paper provides a review of the latest development in ATMSM by evaluating the current techniques in the industry and by analyzing technical data obtained from an extensive experimental program.